Determination of biologically active compounds in lipophilic extracts of pumpkin using thin layer chromatography - E. A. Degtyaryovа; V. A. Grudko; L. I. Vishnevskaya; E. I. Bisaga (Zaporozhye State Medical University, 2015)
Aim. Carotenoids are a common and important class of natural fat-soluble pigments. The prevention of free radicals formation is the carotenoid's primary effect. One of the tasks while creating medicines which contain carotenoids is the identification of them in plant objects. Methods and results. Our purpose is the determination of biologically active compounds in lipophilic extracts of pumpkin using thin layer chromatography. The article presents the experimental study of solvent systems. Although, different developers which are recommended in literature have been chosen and investigated, As a result biologically active compounds of the lipophilic character have been identified, β-carotene has been identified, solvents and reagents for the identification of β-carotene have been selected. Conclusion. This method can be included to the quality control methods to determine β-carotene in the lipophilic pumpkins extracts.